Septic Abortion due to Streptococcus pneumoniae: a rarity - Case report - Ahmed, Imran; Jabeen, Kauser; Naz, Sumaira; Zafar, Afia (Infectious Diseases Journal of Pakistan, 2023)
It is very rare to find Streptococcus pneumoniae causing septic abortion. This case report describes a case of septic abortion attributed to S. pneumoniae. The pathogen was isolated from high vaginal swab and blood cultures of the patient. The patient was treated successfully and discharged in stable condition. This case report highlights the significance of pneumococcus in septic abortion and emphasizes upon microbiology laboratory personnel the importance of correlating cultures with clinical findings of patients. Key words: Case report, Septic abortion, Streptococcus pneumoniae